Resist to the end : Hong Kong, 1941-1945 - Barman, Charles (Royal Asiatic Society Hong Kong studies series., 2009)
Charles Barman was a Quartermaster Sergeant in the Royal Artillery during the battle for Hong Kong in December 1941. Here, Barman offers a description of the fighting in Hong Kong as well as his subsequent imprisonment.